Self -Reported Symptoms of Depression and Associated Features in Medical Interns at a South African Tertiary Health Facility - Naidu, Kaveshin (Department of Psychiatry and Mental Health, 2022)
Background: It is known that medical doctors suffer from increased rates of depression with medical interns being most at risk. Despite this, little is known about the prevalence of depression in interns in South Africa. Aim: This study aimed to assess the prevalence of depressive symptoms in interns. Setting: All 91 interns employed at Groote Schuur Hospital, a tertiary hospital in the Western Cape, from January 2017 until May 2018, were invited to participate in the study. Methods: The study was a cross-sectional study. Consenting interns were required to complete a demographic and related questionnaire and the Beck Depression Inventory 2 (BDI-2). Results: Fifty-four (59.3%) of all invited interns participated in the study. Twenty-two interns (41%) reported a Beck Depression Inventory 2 score of 14 or greater. Features associated with a BDI-2 score of 14 or greater, included female gender, a previous diagnosis of depression, seeing a psychotherapist and previously being on antidepressant medication during internship. Other features also significantly associated with higher BDI-2 scores included, suicidal ideation, thoughts of emigration, wanting to leave Medicine and using substances to cope. The most significant associated feature of high BDI-2 scores was feeling “burnt out”. Conclusion: Interns had a higher prevalence of depressive symptoms when compared to the general population. The feeling of being ‘burnout' was the most significant factor associated with the severity of depressive symptoms. It is imperative that the mental health of both medical students and newly qualified doctors be prioritised, supported and monitored.